Nuovi documenti per lo studio della spedizione Nobile al Polo nord - S. Morosini; S. A. Twardzik (Edizioni Ca' Foscari - Venice University Press, 2023)
This essay examines recently discovered archival documents revealing the administrative and financial aspects of the 1928 Umberto Nobile expedition to the North Pole. Preserved in Milan’s Municipal Archives, these documents shed light on Italy’s commemorative efforts following World War I and its pursuit of international recognition. The essay explores how fascist Italy employed scientific missions, including Nobile’s expedition and Prince Aimone’s Karakorum expedition, to project power and advance geopolitical interests. It delves into the complex interplay between propaganda, foreign policy, and Italy’s engagements within and outside of Europe. By providing valuable historical insights, these newly uncovered documents deepen our understanding of the Nobile expedition and its significance within the broader context of Italy’s fascist era.